Odpowiedź :
Odpowiedź:
A= -21
B= 48
C= -16
D= -2
E= -4
F=0
G= -4
H= -1
Szczegółowe wyjaśnienie:
na lekcji sprawdzane i było dobrze
Odpowiedź:
a)
(-2 + 9) * (-3) = 7 * (-3) = -21
b)
(-4 - 8) * (7 - 11) = -12 * (-4) = 48
c)
-4 * 5 - 7 * (-2) = -20 + 14 = -6
d)
[3 - (-5)]/-4 = (3 + 5)/-4 = 8/-4 = -2
e)
(-16 - 8) : (-4 + 10) = - 24 : 6 = -4
f)
(-2) * (5 - 9) - (-7 + 3) = -2 * 4 - (-4) = -8 + 4 = -4
g)
-7 + 8 : (-2) - 3 * (-5) = -7 - 4 + 15 = -11 + 15 = 4
h)
[(14 - 19)) - (27 - (-3))]/(20 - 25) = [-5 - (27 + 3)]/-5 = (-5 + 30)/-5 = 25 : (-5) = -5
Szczegółowe wyjaśnienie: